Metodologia para alocação de fluxos e perdas no sistema de transmissão em mercados elétricos tipo pool-bilateral - Vila, Clodomiro Unsihuay (2003)
In order to promote the competition and economic efficiency in electric energy markets, it has been established the transmission open access. In consequence, it is necessary to allocate the transmission cost between all of the transmission users. In most of literature work, costs due to the utilization of the transmission system and transmission loss are allocated according to the level of power flowing in the network. Thus, an accurate and non discriminatory decomposition of flows and losses into individual contributions for each market agent is imperative. Nevertheless, this is a complex, non trivial problem, mainly because of the non linear nature of the power flow and losses. In this dissertation, a methodology for transmission utilization and losses allocation under pool-bilateral electricity markets is proposed. The methodology uses the power flow base case, combined with electric circuit techniques and a decomposition transaction pairs energy based scheme. Our model is accurate in the decomposition of the power flows and losses in the transmission system branches for each market agent, whether or not it is operating within a pool type, bilateral contract market or in both. Moreover, our method also computes the nodal allocation and decomposition of the power flows and losses for each agent, exactly reflecting the branches allocations and decompositions at each bus system. For comparison and analysis of the proposed approach, several tests have been done using the following test systems: a 5-bus system; IEEE-14 and IEEE-118 systems. Results and comparisons with other three methods clearly illustrate the better performance of the proposed methodology.